Labour market policy in OECD countries – selected aspects - Knapińska, Magdalena; Woźniak-Jasińska, Katarzyna (Publishing House of Wroclaw University of Economics and Business, 2024)
The goal of the paper was to evaluate OECD countries in terms of labour market policy, and to create a measure allowing to divide the analysed countries according to public spending on labour market policy. Dealing with crises caused by exogenous and endogenous factors mainly consists in activating macroeconomic policy instruments, which requires a deeper analysis. One of the objectives of macroeconomic policy is full employment, pursued in particular through labour market policies – and this aspect of the state’s activities is presented extensively in the paper. First, on the basis of the OECD database, an analysis was made of the amount of funds spent on labour market policy: active and passive, measured as the percentage of the GDP of a given country. Secondly, based on the TOPSIS method and the CRITIC method, a synthetic measure with regard to public spending on labour market policy was created. These methods enabled to group the countries according to the number of these measures as well as in terms of the importance of labour market policy within macroeconomic policy. Thus countries were assigned to the labour market policy models analysed and presented in the earlier literature. Research method: literature analysis (OECD reports), analysis of statistical data from the OECD database with the use of descriptive statistics methods, logical inference, analysis of cause-effect relationships, the Technique for Order Preference by Similarity to an Ideal Solution (TOPSIS) method, the Criteria Importance Through Intercriteria Correlation (CRITIC) method. Hypotheses: OECD countries are diversified in terms of the labour market policy (measured as % of GDP); an active labour market policy plays a more important role in OECD countries than a passive one; the assignment of countries to the labour market policy models discussed earlier in the literature has changed. Results: The analysis showed that the examined OECD countries were diversified in terms of labour market policy, as they focused on different instruments of this policy. However, the level of public spending on labour market policy increased in most countries in the period 2007-2019. Based on the employed methods, the author divided the OECD countries into four groups in terms of the role of labour market policy, and stated that in some OECD countries (e.g. Scandinavia), the policy on labour market (LMP) corresponded to the classification of models of LMP in the literature. Other OECD countries represented different models of LMP and different values of a synthetic measure and, in their case, this study did not confirm compliance with the theoretical models, however this could have resulted from the specification of the research or the change in the specific nature of labour market policy in these countries. Value added: The literature offered varied typologies of labour market policy, most often derived from the models of implemented economic and social policy. This study contributes to the literature by investigating empirically the selected OECD countries in terms of labour market policy, and also compared the results with existing models of labour market policy in the literature.
Argumenta Oeconomica, 2024, Nr 2 (53), s. 186-199
Keywords: labour market; labour market policy; OECD countries; economic policy